2019
DOI: 10.1177/1933719118815582
|View full text |Cite|
|
Sign up to set email alerts
|

Methylseleninic Acid Suppresses Breast Cancer Growth via the JAK2/STAT3 Pathway

Abstract: Previous studies show that methylseleninic acid (MSA), which is the most common selenium derivative used as a drug in humans, exerts specific cytotoxic effects in several cancer cell types. However, the complex mechanism of these effects has not been fully elucidated. Here, we demonstrate by Cell Counting Kit-8 in mouse breast cancer cell line 4T1 that MSA inhibits cell viability in a concentration-dependent (5, 10, 20 μmol/L) and time-dependent (6, 12, 24 hours) manner. Flow cytometry, Western blot, and Rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Other compounds target different signaling pathways, including the JAK2/STAT3 and Akt pathways. Both ganoderic acid A, which is isolated from ganoderma, and methylseleninic acid are found to suppress breast cancer proliferation via the JAK2/STAT3 pathway [82,83]. A compound called caffeic acid p-nitro-phenethyl ester (CAPE-pNO 2 ) is found to inhibit the EGFR/STAT3/Akt pathway and suppress breast cancer proliferation and metastasis [88].…”
Section: Advances In the Study Of Compounds Targeting Stat3 In Breastmentioning
confidence: 99%
“…Other compounds target different signaling pathways, including the JAK2/STAT3 and Akt pathways. Both ganoderic acid A, which is isolated from ganoderma, and methylseleninic acid are found to suppress breast cancer proliferation via the JAK2/STAT3 pathway [82,83]. A compound called caffeic acid p-nitro-phenethyl ester (CAPE-pNO 2 ) is found to inhibit the EGFR/STAT3/Akt pathway and suppress breast cancer proliferation and metastasis [88].…”
Section: Advances In the Study Of Compounds Targeting Stat3 In Breastmentioning
confidence: 99%
“…8,[16][17][18] As a cytokine, the transcription factor STAT3, has been testified that it is closely associated with tumor development. STAT3 can inhibit apoptosis and autophagy, [19][20][21] and promote migration/ invasion 16,22,23 of primary cancers, such as liver cancer. After activation, STAT3 will translocate into the nucleus and regulate transcription.…”
Section: Introductionmentioning
confidence: 99%
“…Using 4T1 mouse malignant breast cancer cells as an example, it was shown that MSA significantly induced apoptosis of these cancer cells by activating Bax, caspase-3, PARP [59]. In addition, MSA was able to inhibit tumor angiogenesis by reducing the expression of vascular endothelial growth factors VEGF and Ang-2 in mammary cells of dogs and mouse models.…”
Section: Reasons and Molecular Mechanisms Of The Cytotoxic Effect Of Msa On Cancer Cellsmentioning
confidence: 99%
“…[ 59,60] WM1552c, UKRV, Colo875 (human melanoma cell lines), SK-BR-3, BT-474 (human mammary carcinoma cell lines), B16F10 (mouse skin melanoma cells)…”
Section: Pel (Primary Effusion Lymphoma)mentioning
confidence: 99%